Where Has All the "Rural" Gone? Rural Education Research and Current Federal Reform - Topper Sherwood (Journal of Research in Rural Education, 2000)
Like the traditional American farmer, the rural education researcher appears to be something of an "endangered species." Rural education research has been misunderstood, underfunded, unencouraged and, taken as a whole, the resulting collection of work has suffered for it, according to many observers. A variety of studies-notably, analyses supported by the U.S. Department of Education itselfidentify significant deficiencies in the national body of research, including available raw data, on rural schools.